Prevalence of irritable bowel syndrome in Chinese college and university students assessed using Rome III criteria - Dong, Yan-Yan (Baishideng Publishing Group Co., Limited, 2010)
AIM: To estimate the prevalence of irritable bowel syndrome (IBS) in college and university students of North China and certain related factors for IBS. METHODS: A total of 2500 students from Shandong University in North China were asked in February-March 2009 to complete questionnaires, including the Rome III questionnaire, hospital anxiety and depression scale, and IBS-quality of life questionnaire (IBS-QOL). RESULTS: Among the 2126 students with complete data, the prevalence of IBS was 7.85% according to the Rome III criteria, with a female/male ratio of 1.78:1. Most students had the IBS-constipation subtype (36.5%), followed by IBS-diarrhea subtype (31.1%) and IBS-mixed subtype (23.9%). The students with IBS had a higher anxiety and depression score than those without IBS. Low exercise level and anxiety indicated a high risk for IBS. The mean score of IBS patients was 74.2 ± 4.242 on the IBS-QOL. CONCLUSION: The prevalence of IBS is 7.85% in Chinese college and university students according to the Rome III criteria. Low exercise level and anxiety may be the risk factors for IBS.